Student Voice in Textbook Evaluation: Comparing Open and Restricted Textbooks - Woodward, Scott; Lloyd, Adam; Kimmons, Royce (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Advocates for student voice in higher education believe students should have the right and power to engage in much of the decision-making traditionally dominated by instructors or administrators. This qualitative study examines the role of student voice in the evaluation of textbook quality. Evaluators included two graduate students enrolled in a project management course at a university in the western U.S. and their instructor. Evaluators used their own student-created metric to analyze the comparative quality of eight graduate-level project management textbooks, two of which were open and six copyright-restricted. The purposes of this study were to assess the comparative quality of low-cost open textbooks and traditional copyright-restricted textbooks and to identify key student-generated criteria wherein all textbooks may be improved to better serve student needs. The analysis revealed that textbooks can be rigorously and meaningfully evaluated by students, that open textbooks can compete with restricted textbooks in terms of quality, and that polyphonic approaches to textbook evaluation can be valuable for learning. We discuss the implications of open textbooks as viable, high-quality classroom options, and the importance of valuing both student voice and instructor perspectives to ensure the highest quality textbook selection for courses in higher education.